2020
DOI: 10.1155/2020/8871981
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiscale Deep Health Indicator with Bidirectional LSTM Network for Bearing Performance Degradation Trend Prognosis

Abstract: As rolling bearings are the key components in rotating machinery, bearing performance degradation directly affects machine running status. A tendency prognosis for bearing performance degradation is thus required to ensure the stability of operation. This paper proposes a novel strategy for bearing performance degradation trend prognosis, including health indicator construction techniques and a performance degradation trend prediction method. To more accurately represent the degradation trend, the multiscale d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this paper, a neural network model based on ResNet-GRU is built. The output of the model is the fusion features index called ResNet-GRU-HI, referred to as ResG-HI for short [29,30]. Figure 4 shows its flow structure.…”
Section: Sensitive Feature Selectionmentioning
confidence: 99%
“…In this paper, a neural network model based on ResNet-GRU is built. The output of the model is the fusion features index called ResNet-GRU-HI, referred to as ResG-HI for short [29,30]. Figure 4 shows its flow structure.…”
Section: Sensitive Feature Selectionmentioning
confidence: 99%
“…Then, two fully-connected layers are used to generate the attention weights. It is computed as, 𝑴 = 𝜎(𝑾 1 (𝑾 0 * 𝑭 𝑎𝑣𝑔 + 𝒃 0 ) + 𝒃 1 ), (9) where 𝜎 is the sigmoid function, 𝑊 0 , 𝑊 1 , 𝑏 0 , 𝑏 1 are the weight and bias of the first and second fully-connected layers respectively, 𝐹 𝑎𝑣𝑔 represents the squeezed state maps from GAP. Finally, the weighted attention weight and the output come from 1D-CNN is used as the last 1D-CNN layer.…”
Section: Network Frameworkmentioning
confidence: 99%
“…It has the advantages of convenience and low cost. After years of research, numerous studies have shown that a single monitoring signal cannot exactly describe the state of machine work for monitoring in advanced manufacture [8][9][10]. With the rapid development of sensing and computing technologies, extracting different kinds features from different sensor signals to represent the tool wear status that makes RUL prediction more reliable [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [19] divided the LSTM into two stages before and after degradation points, obtaining different degradation features and using them as LSTM inputs to achieve higher prediction accuracy. Wang et al [20] proposed a method that decomposes fused features on multiple scales and removes high-frequency components to reduce volatility, then combines stacked self-encoders with Bi-LSTM models to achieve high-quality feature extraction and satisfied precision. Wang et al [21] proposed a prediction model of LSTM under an attention mechanism, which makes full use of past information under long sequences to improve the prediction ability.…”
Section: Introductionmentioning
confidence: 99%